2021
DOI: 10.1080/01425692.2021.1878873
|View full text |Cite
|
Sign up to set email alerts
|

Intervention culture, grouping and triage: high-stakes tests and practices of division in English primary schools

Abstract: This paper explores the practices of division in operation in primary schools in England in response to the pressures of high stakes tests at age 10/11, known as SATs. Using data from interviews with 20 primary headteachers and information from a survey of nearly 300 primary heads, we argue that the organisation of pupils in preparation for SATs involves 1) the use of grouping by 'ability' in sets, despite the increasing evidence of the disadvantages; 2) forms of educational triage, where borderline or 'cusp' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…It is implicitly linked to the pressure of accountability and audit culture (Marks, 2014). It sets a benchmark for those students who the schools think might be worth working on by deploying additional resources compared to the hopeless group who will not be able to attain the target (Bradbury et al, 2021). Ball and Olmedo (2013) examined that schools make a deliberate attempt to avoid the poor performing students at the institutional level within the educational market.…”
Section: Resultsmentioning
confidence: 99%
“…It is implicitly linked to the pressure of accountability and audit culture (Marks, 2014). It sets a benchmark for those students who the schools think might be worth working on by deploying additional resources compared to the hopeless group who will not be able to attain the target (Bradbury et al, 2021). Ball and Olmedo (2013) examined that schools make a deliberate attempt to avoid the poor performing students at the institutional level within the educational market.…”
Section: Resultsmentioning
confidence: 99%
“…To address these questions the selected research design was a mixed methods concurrent design featuring: (a) a systematic qualitative meta‐synthesis (SQMS); and (b) a questionnaire survey of teachers. The design of the survey was influenced by the authors' experience in large‐scale surveys of teachers (see Bradbury, 2018; Bradbury et al, 2021; Wyse & Ferrari, 2014), and initial work that had located relevant systematic reviews and meta‐analyses (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Another important influence on curriculum and teaching is the nature of national assessment systems which may influence teachers' approaches and schools' policies. For instance, it has been shown that in England the ‘high stakes’ nature of statutory assessments at age five/six, six/seven and ten/eleven have had an impact on teaching (Bradbury, 2018; Bradbury et al, 2021). To determine what is effective teaching of reading, and hence to be reflected in education policy, requires consideration of a range of evidence in order to identify the most robust sources.…”
Section: Introductionmentioning
confidence: 99%
“…At primary school level -the focus of this paper -ability grouping is less common but is increasingly becoming standard practice. Some authors have argued that pressures on schools and teachers to raise standards and meet attainment targets are partly driving this trend (Bradbury, Braun & Quick, 2021;Bradbury & Roberts-Holmes, 2017;Marks, 2016). While fewer than 3% of primary schools reported streaming pupils by ability in the early 1990s (Lee & Croll, 1995), by 2008 16% of 7 year olds were being streamed by ability for all subjects, 26% were being taught in ability sets for both English and Maths, and a further 11% were set for either English or Maths (Hallam, 2012;.…”
Section: What Do We Know About Ability Grouping In the Uk?mentioning
confidence: 99%